Averaging of integral functionals related to domains of frame-type periodic structure with thin channels - Kovalevskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish the Γ-convergence of a sequence of integral functionals related to domains of frame-type periodic structure with thin channels. We obtain a representation for the integrand of a Γ-limit functional.